Ketamine and other glutamate receptor modulators for depression in adults. (July 2016) - Caddy, Caroline; Amit, Ben H.; McCloud, Tayla L.; Rendell, Jennifer M.; Furukawa, Toshi A.; McShane, Rupert; Hawton, Keith; Cipriani, Andrea
Abstract : Considering the ample evidence of involvement of the glutamate system in the pathophysiology of depression, pre-clinical and clinical studies have been conducted to assess the antidepressant efficacy of glutamate inhibition, and glutamate receptor modulators in particular. This review focuses on the use of glutamate receptor modulators in unipolar depression.